Perbedaan Efektifitas Rebozo dan Gymball terhadap Penurunan Intensitas Nyeri Punggung Ibu Hamil Trimester III - Hurin'in, Nur Maziyah; Agustina, Reinita (Universitas Muhammadiyah Pekajangan Pekalongan, 2025)
Low back pain is common during pregnancy; Rebozo technique and Gym Ball are potential non-pharmacological interventions. However, a direct comparison of their effectiveness in the third trimester is still limited. This study aimed to compare the effect of the Rebozo technique versus Gym Ball on low back pain in third-trimester pregnant women. A quasi-experimental study using a non-equivalent control group design involved 32 third-trimester pregnant women (16 Rebozo group, 16 Gym Ball group) selected via purposive sampling. Pain was measured before and after the intervention using questionnaires and observation sheets; data were analyzed using the Mann-Whitney test (α=0.05). Both groups experienced a reduction in pain. The Mann-Whitney test showed a significant difference between the two techniques (U=25.5; p<0.05). The Gym Ball group showed a greater reduction in pain (total rank reduction 302) compared to the Rebozo group (total rank reduction 229). Gym Ball use was more effective than the Rebozo technique in reducing low back pain among third-trimester pregnant women in this study